The Effect of Tax Planning and Leverage on Firm Value with Firm Size as a Moderating Variable - Putra, Samuel Niko; Edastami, Mayangsari (Universitas Batanghari Jambi, 2024)
This study aims to examine the influence of tax planning and leverage on firm value using firm size as a moderating variable. The model employed in this study is a descriptive quantitative research design using secondary data. The population in this study includes consumer goods sector companies listed on the Indonesia Stock Exchange from 2018-2023. The sample selection process used a purposive sampling method, resulting in 156 observations from 26 companies selected as samples. Hypothesis testing is conducted using a moderation analysis model. The results of the study indicate that tax planning affects firm value and leverage affects firm value. Firm size as a moderating variable is capable of moderating the influence of tax planning and leverage on firm value.